Digitalization and sustainability in German continuing education - Derksen, Felix [Verfasser]; Dörpinghaus, Jens [Verfasser] (My University, 2023)
„Skills and qualifications are at the heart of designing digitalized and sustainable futures, as they link society and the labour market. While the design of digitalized futures raises several issues for society, society in turn, and in particular skills and qualifications, can be a bottleneck for maintaining productivity and the workforce. The labor market relies heavily on both vocational and academic education and training, retraining, and continuing professional development to meet these future challenges. Thus, at the individual level, the question arises as to what qualifications and skills are needed in a digitalized and sustainable future. In this paper we present a novel approach to analyze advertisements for continuing vocational education and training (CVET) in order to identify if skills and qualifications needed for digitalization and sustainability are currently considered, and if the so-called green economy is also important for CVETs.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 6 Berufsbereiche; 370; 330; Weiterbildung; Stellenanzeige; Datenanalyse; Berufsklassifikation; Qualifikationsanforderung; Anforderungsprofil